Young Children’s Creation of Drawings in Mathematics - Bakar, Kamariah Abu; Yunus, Faridah; Mohamed, Suziyani (International Journal of Psychosocial Rehabilitation, 2020)
Young children enjoy drawing activities and naturally expressed their feelings through their self-created drawings. However, the creation of drawings as a means for communicating mathematical thinking, learning and understanding in the early years of school has not been the focus of many researchers. This paper investigates young children’s production of drawings for the topic of small number and basic addition operation. Data collection included artifact (children’s drawing), observations, filed notes, conversations with children and video recording of children completing posed tasks. The findings exhibited that children struggled to use drawing as a mathematical representation tool but continuous prompt and encouragement from the researcher has led to the production of two types of representation (i.e. pictographic and iconic drawings). Further analysis on the children’s drawings as well as action, behaviors and talk provided insight into their understanding of small numbers and addition concept. This study implicated that the creation of drawing is beneficial in developing young children learning as well as an understanding of mathematics concepts.